(untitled) (Current Horticulture, 2024)
The experiment was conducted to optimise doses of NPK for curd yield in broccoli during rabi 2018-19, 2019- 20 and 2020-21. There were 3 factors i.e. nitrogen @ 100, 150 and 200 kg/ha, phosphorus and potash each @ 50 & 75 kg/ha comprising 12 treatments. Significant increase was found in plant height, plant spread, number of leaves/plant, stem diameter, leaf length, curd weight, curd length, curd diameter, yield /plot, curd yield. The decrease in days to 50% in curd formation and days to final harvest were recorded with different levels of NPK doses. Growth and yield attributes were maximum with 200:75:50 NPK kg/ha which was at par with 150:75:50 NPK kg/ha.